ضوابط عمل المرأة في الفقه اإلسالمي: مفهومها وحقيقتها Controls of women’s work in Islamic jurisprudence: their concept and reality - Mohammed Idris, Kabir; Hj Ibrahim, Badruddin (Al Hikmah Research and Publication Centre, 2022)
This research explored an important issue of control measures put by Islam on women before leaving homes for public and private work.. The intention and motive of these restrictions is to preserve women and also maintaining their dignity. Also these control measures are meant to block doors of sedition. The paper explores the need for women to leaving homes today in the name of working in public services and fields. This paper will try to explore the legal control measures set by Islam for women who want to leave homes for general issues and work related in public spheres. The paper explores what women should abide by before going out to work. Exploring characteristics of the garments they should put on that are in line with the Islamic veil. Also the researcher explored control measures on the nature of work women should indulge in. one of the most important findings of this research is that, Islam did not prevent women from practicing the profession of work, but rather set conditions and control measures that should be observed by husband and those who have a responsibility on women before leaving homes. People we live with whether wives, daughters or sisters, should be given advice, guidance and reminders on the basic responsibilities they hold. It’s in their mandate to take care of home affairs and to raise children. Women should hold works that allows them to practice their domestic roles and work duties. And not neglect one side at the expense of one side. The researcher relied on the secondary source to collect scientific material from heritage books, articles, tracking opinions and evidence of Islamic scholars, and then used the analytical approach to analyze and discuss these data sources.